2022
DOI: 10.1021/acs.iecr.2c01191
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Segregation in the Dilute Phase Transport of Nonspherical Particles through a Pneumatic Conveying System

Abstract: The current study aims to investigate the segregation in the dilute phase transport through a pneumatic conveying system. Different types of nonspherical particles such as ellipsoids (prolate and oblate), cube, and elongated needles are mixed with spherical particles to study the influence of nonsphericity. Experiments are performed to examine the effects of particle and system parameters such as particle size, particle shape, gas velocity, and solid loading rate on segregation. A unique decreasing segregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Particle flocs formed by quartz sand with an average particle size of d = 0.25 mm were investigated, and it was found that the method was able to accurately identify "U"-shaped, inverted "U"-shaped, and bar-shaped particle clusters. Verma 23 used a high-speed video camera in his experiments to acquire nonspherical particles in a pneumatic conveying system with dilute-phase transport polarization, and the study shows that the difference in particle size affects segregation significantly. Gas−solid phase flow is very complex 44 and encompasses interactions between the fluid phase and the solid phase as well as between the solid phase and the solid phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle flocs formed by quartz sand with an average particle size of d = 0.25 mm were investigated, and it was found that the method was able to accurately identify "U"-shaped, inverted "U"-shaped, and bar-shaped particle clusters. Verma 23 used a high-speed video camera in his experiments to acquire nonspherical particles in a pneumatic conveying system with dilute-phase transport polarization, and the study shows that the difference in particle size affects segregation significantly. Gas−solid phase flow is very complex 44 and encompasses interactions between the fluid phase and the solid phase as well as between the solid phase and the solid phase.…”
Section: Introductionmentioning
confidence: 99%
“…With the realization of mankind that the use of traditional energy sources has had a serious impact on the environment and climate change, the use of clean energy has received increasing attention from countries around the world. As a kind of green, low-carbon, and clean energy, biomass can be widely used in industry, life, transportation, and other fields. In biomass energy, the pneumatic conveying device is an efficient gas–solid reaction and heat and mass transfer equipment, which has many advantages, such as fast gas–solid transfer speed, high contact efficiency, and high utilization of raw materials and equipment. Therefore, pneumatic conveying devices are widely used in the conversion process of biomass energy, which makes an essential contribution to the development of the clean energy industry. After nearly 70 years of fundamental theoretical research and technological development, pneumatic conveying devices are now widely used in many industries, such as the chemical industry, energy, food processing, material processing, environmental protection, and so on. Some of the advantages of pneumatic conveyors are the low number of moving parts, flexible setup, and fully enclosed transportation, all of which create environmentally safe applications . It serves not only as an alternative for transporting pellet materials between locations or blending different pellet types but also facilitates the prefabrication of biomass pellets, offering functionalities such as moisture content control, sorting, feed, and mixing. In the realm of contemporary engineering applications, there is a prevailing preference for dilute-phase conveying, which proves to be the most economical mode due to the inherent ease of cleaning and maintenance associated with the equipment compared to concentrated-phase conveying systems . During system operation, the conversion of energy generated in the braking process into electricity allows for effective energy recovery, contributing to a reduction in the overall energy consumption of the system .…”
Section: Introductionmentioning
confidence: 99%
“…There has been a significant amount of research on the segregation of granular materials due to their practical importance, and efforts have been made to understand the fundamental principles involved. Granular materials have a tendency to segregate during flow when there are differences in particle characteristics such as cohesiveness, shape, size, and density 32–36 . Three frequent mechanisms have been proposed to explain the segregation/mixing behavior of particles, which includes percolation, 37–40 buoyancy, 33,41 and convection 42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Granular materials have a tendency to segregate during flow when there are differences in particle characteristics such as cohesiveness, shape, size, and density. [32][33][34][35][36] Three frequent mechanisms have been proposed to explain the segregation/mixing behavior of particles, which includes percolation, [37][38][39][40] buoyancy, 33,41 and convection. 42,43 The mechanisms of segregation in the system are percolation and buoyancy, while convection is the mechanism responsible for mixing.…”
mentioning
confidence: 99%
“…Granular materials have a tendency to segregate during flow when there are differences in particle characteristics such as cohesiveness, shape, size, and density 26,27,28,29,30 . Three frequent mechanisms have been proposed to explain the segregation/mixing behavior of particles, which includes percolation 31,32,33,34 , buoyancy 27,35 , and convection 36,37 .…”
Section: Introductionmentioning
confidence: 99%